A Socio-Pragmatic Analysis of Women’s Speech in Naguib Mahfouz's Walk Palace - Asran, Nahla Hashem Abdel-Galiel (جامعة سوهاج - كلية الآداب, 2018)
This study is a socio-pragmatic study that is related to the branch of linguistic anthropology (culture, language, and society). Thus, the speech of the main female characters of Walk Palace is analyzed and discussed qualitatively and quantitatively. Also, this study discusses the linguistic features that have been attributed to women‟s language, arguing that women could reach their needs through using language without more intellectual work to determine the linguistic features either verbally or non-verbally that should be used in a certain situation or context. That is why they depend on their social behaviors in the speech community that they acquire from the surrounding social communicative environment.
Keywords: الرواية -- التحليل الاجتماعي -- المرأة المصرية -- الخطاب النسوي -- المجتمع المصري -- رواية بين القصرين -- محفوظ، نجيب